Leave Her out of It: Person‐Presentation of Strategies is Harmful for Transfer. (21st March 2015) - Riggs, Anne E.; Alibali, Martha W.; Kalish, Charles W.
Abstract: A common practice in textbooks is to introduce concepts or strategies in association with specific people. This practice aligns with research suggesting that using "real‐world" contexts in textbooks increases students' motivation and engagement. However, other research suggests this practice may interfere with transfer by distracting students or leading them to tie new knowledge too closely to the original learning context. The current study investigates the effects on learning and transfer of connecting mathematics strategies to specific people. A total of 180 college students were presented with an example of a problem‐solving strategy that was either linked with a specific person (e.g., "Juan's strategy") or presented without a person. Students who saw the example without a person were more likely to correctly transfer the novel strategy to new problems than students who saw the example presented with a person. These findings are the first evidence that using people to present new strategies is harmful for learning and transfer.